A Miniature Endoscopic Optical Coherence Tomography Probe Based on C-Lens - Site Luo; Liang Zhou; Donglin Wang; Can Duan; Hao Liu; Yu Zhu; Guoxin Li; Hui Zhao; Jianyu Tang; Yuqing Wu; Xin An; Xinling Li; et al. (IEEE Photonics Journal)
We present a novel miniature endoscopic optical coherence tomography (OCT) probe based on an electrothermal microelectromechanical (MEMS) mirror and a C-lens. The MEMS mirror has a relatively large mirror plate of 0.5 mm × 0.5 mm on a small chip size of 1.5 mm × 1.3 mm, leading to the outer diameter of the endoscopic probe down to only 2.5 mm so that the probe is capable of being inserted through the biopsy channel of a conventional endoscope. A long focal length of 12 mm is achieved by properly designing the C-lens. Compared to commonly used GRIN lenses, C-lenses have advantages of much smaller sensitivities of the working distance and spot size to machining variations. The C-lens based probe can scan a large field of view (FOV) of 6 mm × 6 mm at only 5-V drive voltage. A swept source endoscopic OCT system is constructed using this miniature probe. Experiments show that the corresponding lateral and axial resolutions are about 50 and 14 μm, respectively. Various samples including human fingers, onions, and cancerous colon tissue are imaged and the result suggests this large-working-distance, large-FOV endoscopic probe is promising for applications in large tubular organs and large-area lesions.